종간교잡 유래 중생 고품질 벼 품종 화원 1호 - 안상낙(Sang Nag Ahn); 구홍강(Hong Guang Ju); 김동민(Dong Min Kim); 오창식(Chang Sik Oh); 강주원(Ju Won Kang); 김봉학(Feong Xue Jin); 오지민(Ji Min Oh) (Korean journal of breeding, 2009)
"화원1호"는 종간교잡을 통해 화성벼의 근동질계통을 육성하고자 '97년 화성벼와 O. rufipogon을 교배하고, 계속적인 여교배와 MAS(Marker aided selection)를 병행 실시하여 CR101-1-1 계통을 선발하였다. 생산력검정 시험 결과 조사된 형질 중 천립중을 제외한 기타 형질에서는 화성벼와 유사한 근동질계통이었으며, 품종보호원 출원 조건에 부합하여 "화원1호"로 명명하고 품종보호원을 출원하였다. 1. 출수기는 보통기재배에서 8월 "Hwaweon 1" was developed from an interspecific cross between Hwaseongbyeo and a wild species, Oryza rufipogon L. (IRGC 105491) based on marker-aided selection. The recurrent parent "Hwaseongbyeo" is a high grain quality cultivar with medium-maturity. Hwaweon 1 is nearly isogenic to Hwaseongbyeo except a small O. rufipogon introgression on chromosome 8 harboring the gene for grain weight. The preliminary and replicated yield trial was conducted at Chungnam National University in 2004, 2005 and 2006. The local adaptability test was carried out by the National Seed Management Office (NSMO) in 2007 and 2008. This cultivar was registered to NSMO with a cultivar designated as "Hwaweon 1". This cultivar averaged 89 cm in culm length and has a medium growth duration. This cultivar is resistant to stripe virus as the recurrent parent, Hwaseongbyeo. Milled rice of "Hwaweon 1" is translucent and the grain quality traits are comparable to those of the recurrent parent. The yield potential of "Hwaweon 1" in grain is about 7.43 MT/ha at the ordinary fertilizer level about 10% higher than that of Hwaseongbyeo mainly due to increase in grain weight.